A Voluntary Gleichschaltung? Indian Perspectives Towards a non-Eurocentric Understanding of Fascism - Benjamin Zachariah (The Journal of Transcultural Studies, 2014)
Using historical material from India, this essay is part of a larger attempt to rethink the Eurocentrism, explicit or implicit, that marks our understanding of fascism, and also to rethink Indian fascism using (often Eurocentric) theories of fascism. It conceives of fascism as a family of ideas, with common––though often disavowed––roots, intellectual underpinnings, styles and organisations of movements, and sometimes even a strong overlap of personnel. The argument hinges on the contention that the emergence of a fascist imaginary and a fascist set of political organisations in the 1920s and 1930s depended to a large extent on what I call a “voluntary Gleichschaltung” of ideas, movements, and institutions, which recognized one another as belonging to the same family, but adopted some of the characteristics of a more successful sibling. A number of these ideas existed in earlier versions from the previous century, and they lent themselves to a fascist repertoire that found its conjuncture between the two world wars––a repertoire that was drawn upon by a number of movements that are entitled to the use of the adjective “fascist.”